Year in review: Critical Care 2004 – nephrology - Ricci, Zaccaria (BioMed Central, 2005)
We summarize all original research in the field of critical care nephrology published in 2004 or accepted for publication in Critical Care and, when considered relevant or directly linked to this research, in other journals. Articles were grouped into four categories to facilitate a rapid overview. First, regarding the definition of acute renal failure (ARF), the RIFLE criteria (risk, injury, failure, loss, ESKD [end-stage kidney disease]) for diagnosis of ARF were defined by the Acute Dialysis Quality Initiative workgroup and applied in clinical practice by some authors. The second category is acid–base disorders in ARF; the Stewart–Figge quantitative approach to acidosis in critically ill patients has been utilized by two groups of researchers, with similar results but different conclusions. In the third category – blood markers during ARF – cystatin C as an early marker of ARF and procalcitonin as a sepsis marker during continuous venovenous haemofiltration were examined. Finally, in the extracorporeal treatment of ARF, the ability of two types of high cutoff haemofilters to influence blood levels of middle- and high-molecular-weight toxins showed promise.